Analysis of the Liability of Capital Market Supporting Notaries for the Contents of the Deed of Corporate Action Backdoor Listing by Limited Liability Companies - Ayu, Tirsa; Sihabudin, Sihabudin; Dewantara, Reka (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
Backdoor listing refers to a situation where an unlisted company obtains listed status indirectly through a listed company. Law Number 8 of 1995 concerning Capital Markets (UUPM) and its implementing regulations that have been enacted in Indonesia to accommodate activities in the capital market do not include detailed arrangements related to backdoor listing corporate actions, resulting in confusion about the practice of backdoor listing itself. This research aims to analyze the responsibility of the Capital Market Supporting Notary for the contents of the deed of backdoor listing corporate action by Limited Liability Companies. the research used in this research is normative legal research, with a research approach to the legislative approach and concept approach used to examine problems related to legal issues. Briefly, the result of the research is that the Notary plays an important role in backdoor listing by making the GMS deed. The main responsibility of the notary is to ensure the deed complies with the regulations. If there is a violation of the law, the notary can be summoned but must be with the permission of the Notary Honor Council.